(3CfSGH Bd GdHjJ hGdCFeIs - (3CHh GdQHjY SdjeGf Hf eMeO Hf YHO Gddg GdTaTGhfj GdaGSj, GdMhGJ,J (B1231 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb Bd GdHjJ ef CfhGQ YXeJg GdJi ChOYgG ai CUdGHge HSGHb bOQJg , hcTa Yf CSQGQgG ai hLhgge HebJVi MceJg s
(3BNQgG (B:s
(3hMGTG jNjH ef jfjN HHGce hcGf GdaQGZ ef JNQjLg ai GdKGef YTQ s
(3JUhjQ HYV GdUaMGJ QOFs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B133s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B53 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs